Partiforskning i komparativ politik - Gauja, Anika; Kosiara-Pedersen, Karina (Politik, 2019)
How are party organisations studied within political science, and in particular, within comparative politics? In this article, we sketch out the tradition and main research contributions and provide theoretical reflections on how parties organize. We address the thesis of party decline of the 1980s and 1990s, and point to the focus on party change, rather than decline, from then on. We show the wealth of party organization studies and focus on the comparative studies, the specialization into subfields of party leadership, candidate nomination, party membership and party financing, and in the final section we point to the newest tendencies of personalization, new forms of affiliation and links to social movements. The overall conclusion is that the research field of political party organizations within comparative politics is, like political science in general, becoming more heterogeneous, specialized and quantified. Fewer general monographs and more journal articles dealing with a limited number of party organization characteristics are published, and while the qualitative research methods have not disappeared, they have given way to much more quantitative studies. There is a link between, on the one hand, how parties of the real world organize as well as the data that researchers have access to, and on the other hand, how the research field develops.